Peran Literasi Keuangan Dalam Menekan Risiko Hukum Investasi Di Pasar Modal Indonesia - Jahraa Salsabiil Bahi Efendi; Indra Nova; Sofi Indriani; Reyvanda Yudi Putra; Radhi Muhammad Arfa; Helfira Citra (CV. ITTC INDONESIA, 2025)
Financial literacy is a fundamental factor in supporting sound investment decision-making and minimizing legal risk in the Indonesian capital market. Low levels of investor financial literacy have the potential to lead to various legal issues, such as misunderstanding the characteristics of investment instruments, legal rights and obligations, and increased vulnerability to illegal investment practices. This study aims to analyze the role of financial literacy in mitigating legal investment risks in the Indonesian capital market. The research method used is a qualitative approach using literature review techniques, sourced from scientific journals, capital market laws and regulations, and official publications of relevant authorities. The results indicate that improving financial literacy can enhance investors understanding of investment law, encourage more rational investment behavior, and raise awareness of available legal protection mechanisms. Thus, financial literacy plays a preventive role in reducing the potential for disputes and legal violations in the Indonesian capital market. This research is expected to serve as reference for regulators, market players, and academics in formulating strategies for improving sustainable financial literacy.